Lessons Learned for REDD+ from PES and Conservation Incentive Programs : Examples from Costa Rica, Mexico, and Ecuador - FONAFIFO; CONAFOR; Ministry of Environment (World Bank, Washington, DC, 2017)
Mexico, Costa Rica, and Ecuador have substantial experience with implementing payments for ecosystem services (PES) and conservation incentive programs. Yet, many aspects of their experiences remain poorly understood and will require special attention in any new or expanded use of these types of incentives. As these countries, along with many others, get ready to implement integrated approaches to Reduced Emissions from Deforestation and Forest Degradation (REDD or REDD+), they seek to understand how the lessons and challenges from their past experiences, as well as the wider lessons from similar initiatives around the world, can inform their emerging REDD+ strategies, policies, institutional frameworks, and tools. This report describes examples of how each of these topics has been tackled in national programs and how these experiences can inform the development of REDD+ in the three focus countries and beyond.